Prevalance Of Health Supplement Products Use And Their Potential Interactions With Drugs Prescribed For The Outpatient Population Of Sarawak District Hospital - Loo, Shing Chyi (2021)
Recently, the use of health supplement products is increasing among public in Malaysia. Nevertheless, there is limited research on the prevalence of health supplement products utilization among Malaysian population. Additionally, previous studies in Malaysia did not properly address the prevalence of concomitant use of prescribed medicines and health supplement products, as well as the practices, perceptions, factors which lead to the use of supplement products, and potential interaction between health supplement products and prescribed medicines among the rural population from Sarawak. This study aims to assess the prevalence of health supplement products consumption, and to identify practices, perception, factors affecting the use of such products, and potential interaction between health supplement products and prescribed medicines among patients with chronic diseases in rural area of Sarawak, Malaysia. This was a multicenters cross-sectional study conducted in outpatient pharmacy department of seven non-specialist government districts Hospitals in Sarawak. A data collection form was developed, and pilot tested prior to the data collection. Data was collected from June to August 2018. Binary logistic regression was used to assess the association between patients’ social demographic characteristics and the consumption of supplement products.